Effects of Laboratory Animal Science Training on Scientists' Attitudes and Practice in Egypt - Gaafar, Khadiga; Fahmy, Sohair R (Journal of the American Association for Laboratory Animal Science, 2018)
The implementation of principles and guidelines that govern the various areas of research in an educational institution is one of the key factors in international recognition of its research integrity and value. The privilege of conducting research using animal subjects requires adherence to international regulations and standards governing the humane care and use of laboratory animals. The IACUC at our university deemed it critical to have an animal care and use training program to raise researchers' understanding and knowledge. Our IACUC recently designed a training program in the principles of laboratory animal science and the ethical issues involved in animal use. The present study aimed to measure the effect of such training on scientists' attitudes and practice. During 4 successive training courses, the participants (n = 100; 72% women and 28% men) were surveyed twice through self-administered questionnaire-before starting and after completing the course. Questions focused on ethical consideration for care and use of animals in research, ethical committees, international guidelines for humane care of animals, and 3Rs concepts and their interpretation. The results revealed that the scientists' knowledge and awareness increased effectively after the completion of the training courses. They understood the 3Rs concepts of replacement, reduction, and refinement; recognized the importance of standardization of animal handling on scientific results; and were able to distinguish between different ethical committees and their roles. Overall, training leads to standardization of animal care and use practices that are vital for the reproducibility of results fundamental to quality scientific research.